Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1001/jamadermatol.2015.5663
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Indoor Tanning and Substance Use Among Colorado High School Students

Abstract: Mr Bell and Ms Sendelweck had full access to all the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 6 publications
3
10
0
Order By: Relevance
“…The likelihood of tanning addiction increased with problem substance use and psychological symptoms. Findings of this study are consistent with other research that has identified use of marijuana, alcohol, illicit drugs, or steroids as correlates of indoor tanning behavior in adolescents (Sendelweck et al, 2016).…”
Section: Behavioral Health Conditions Associated With Tanning Addictisupporting
confidence: 91%
“…The likelihood of tanning addiction increased with problem substance use and psychological symptoms. Findings of this study are consistent with other research that has identified use of marijuana, alcohol, illicit drugs, or steroids as correlates of indoor tanning behavior in adolescents (Sendelweck et al, 2016).…”
Section: Behavioral Health Conditions Associated With Tanning Addictisupporting
confidence: 91%
“…According to the 2009 YRBS, male high school students who tanned indoors were more likely to have ever taken steroids without a physician's prescription, used unhealthy weight‐control practices, engaged in binge drinking, and attempted suicide . In a survey of Colorado high school students, use of steroids, alcohol, marijuana, and illicit drugs was positively associated with indoor tanning . In young women, indoor tanning was associated with substance and alcohol use …”
Section: Melanoma Prevention and Early Detectionmentioning
confidence: 99%
“…105 In a survey of Colorado high school students, use of steroids, alcohol, marijuana, and illicit drugs was positively associated with indoor tanning. 106 In young women, indoor tanning was associated with substance and alcohol use. 107,108 Motivations for tanning.…”
Section: Indoor Tanningmentioning
confidence: 99%
“… 51 Similar findings were also observed among Colorado high school students with associations found between indoor tanning and alcohol use, cigarette smoking, marijuana use, and steroid abuse. 52 …”
Section: Teens Young Adults and Indoor Tanningmentioning
confidence: 99%